Flow Diversion in Ruptured Blood Blister Aneurysms: Single Centre Experience - Dilip Kumar; Rahul K. R.; Santhosh P.; Pankaj Mehta; Mathew Cherian; Dharav Kheradia; Rinoy R. Anand (Journal of Clinical Interventional Radiology ISVIR)
Blood blister aneurysms are extremely rare, and its treatment continues to be controversial. Although surgery was the only available treatment a decade ago, today newer endovascular devices such as flow diverters (FDs) appears to have very low complication rates with good long-term results. We analyzed our data of seven patients who angiographically had features of a blister aneurysm. All these patients presented with subarachnoid hemorrhage (SAH). Six of these were in anterior circulation, all of which were in internal carotid artery (ICA) and one was in a P1 segment of posterior cerebral artery (PCA). All of the patients except one in PCA were treated with FDs. One of the patients died (14.3%) following the procedure secondary to thrombosis of FD. Rest of the patients did well postprocedure with the good clinical outcome (modified Rankin Scale [mRS] of less than or equal to 2 at 1-month follow-up) in 85.7% patients. Five of the patients showed complete obliteration of an aneurysm (83.3%) on 6-month follow-up angiography. The only patient with an aneurysm in PCA showed persistence of an aneurysm and this particular lesion was instead treated by a single stent. Blister aneurysms pose diagnostic and therapeutic challenges and demand prompt treatment. Considering that all patients who were treated with FD had complete obliteration, it can be inferred that FD can be the treatment of choice in patients with blister aneurysms presenting with SAH. Further, with the introduction of small vessel FD, thrombotic complications may reduce, lowering the morbidity and mortality. Isolated stenting may not be an optimal treatment of a blister aneurysm.